Heat shock protein bystander antigens for peptide immunotherapy in autoimmune disease. (3rd December 2012) - Zonneveld‐Huijssoon, E.; Albani, S.; Prakken, B. J.; van Wijk, F.
Summary Mucosal administration of an antigen eliciting bystander suppression at the site of inflammation results in effective antigen‐specific immunotherapy for autoimmune diseases. Heat shock proteins are bystander antigens that are effective in peptide‐specific immunotherapy in both experimental and human autoimmune disease. The efficacy of preventive peptide immunotherapy is increased by enhancing peptide‐specific immune responses with proinflammatory agents. Combining peptide‐specific immunotherapy with general suppression of inflammation may improve its therapeutic effect.